(untitled) (Scientific journal of the Fergana State University, 2024)
Science knows 24 subfamilies, 510 genera and 5109 species belonging to the aphid family (Aphididae). Most aphids specialize in feeding on a specific type of plant, but some species can feed on hundreds of unrelated plants. Many authors have emphasized this (Dransfield and Brightwell, 2023; Singh and Singh, 2020; ). Taking these features into account, research work on the study of juices was carried out in the valley regions. This article presents new information on the study of aphidofauna.